مدى مساهمة لجان التدقيق في تعزيز الرقابة الشرعية في المصارف الإسلامية السورية - دراسة ميدانية- - دحدوح, حسين أحمد; مراد, درويش فيصل (Latakia University Journal - Economic and Legal Sciences Series, 2016)
هدفت هذه الدراسة إلى بيان مدى مساهمة لجان التدقيق في تعزيز الرقابة الشرعية في المصارف الإسلامية السورية، ولتحقيق هذا الهدف قام الباحث بإعداد استبانة وزعت على عدد من المدققين الشرعيين الداخليين وموظفي إدارة العمليات المصرفية في المصارف الإسلامية السورية، وخلصت الدراسة إلى أن لجنة التدقيق تسهم في تعزيز الرقابة الشرعية في المصارف الإسلامية ،وذلك من وجهة نظر عينتي الدراسة، وأهم ماتوصي به الدراسة ضرورة توجيه لجنة التدقيق في المصارف الإسلامية لتفعيل دور وظيفة التدقيق الشرعي الداخلي في المصارف الإسلامية- في سورية للمحافظة على سمعة المصرف والتزامه بأحكام الشريعة الإسلامية. This study aimed to show the extent of the contribution of audit committees in strengthening Sharia Control in Syrian Islamic banks, to achieve this goal the researcher prepared a questionnaire was distributed to a number of internal Sharia Auditor and staff management of banking operations in Syrian Islamic banks, the study concluded that the functions of the Audit Committee affect strengthen Sharia Control in Syrian Islamic banks and so from the standpoint of my sample study, the study concluded a series of recommendations including the need for the guidance of the audit Committee in the Islamic banks to activate and the role of the Sharia internal audit function in the legitimate Islamic banks in Syria to maintain the reputation of the bank and its commitment to the provisions of Islamic Sharia.